AI-DRIVEN PHOTOGRAPHY CURRICULUM FOR ART SCHOOLS - Singh, Ritesh Kumar; Rathour, Abhinav; Jena, Shakti Prakash; Pandey, Sonia; Mishra, Abhinav; Kalpana K (ShodhKosh: Journal of Visual and Performing Arts, 2025)
The adoption of the Artificial Intelligence (AI) in art education has provided a paradigm shift in the teaching, learning, and practice of photography. The proposed AI-based Photography Curriculum at the Art Schools is expected to balance the principles of traditional photography and the latest AI technologies so that the students are able to combine the capability to creatively explore the new technologies and the ability to master the camera. The modules are dedicated to automated image curation, style transfer, facial recognition ethics, and intelligent editing tools, which will introduce students to the nature of AI-based artistic processes in their entirety. The curriculum is also pedagogically based on a hybrid approach that integrates theory, real life learning, and project based experimentation. Algorithms efficiency is measured using quantitative performance, such as the accuracy of object recognition and the accuracy of image classification, whereas creativity, originality, and conceptual knowledge are evaluated with the help of qualitative measurement. The incorporation of mathematical underpinnings enhances insight into the process in which the neural networks acquire visual information. As well, AI-generated art, authorship rights, and data bias have ethical aspects ingrained into them to promote responsible artists. The future of the paradigm of education of photography as an art is the product of this AI-driven curriculum that is destined to help future artists find their way in the unstable overlap of technology and imagination.